Contested legalities, (de)coloniality and the state : understanding the socio-legal tapestry of Pakistan - Saeed, Raza (2014)
The study develops two significant arguments in relation to Pakistan’s socio-legal situation and analysis. First, it outlines and discusses the various prominent facets of the country’s legal architecture to formulate and present, what the thesis terms as, Pakistan’s Socio-Legal Tapestry. It considers the historical and conceptual trajectories of some of the multiple legal and normative structures that prevail in the country, their interplay and encounters, as well as their limitations and problems. It puts this socio-legal architecture at the heart of the examination, and by making the different constituents of the legal terrain explicit – components that include common law, Islamic law, colonial law, traditional law, legal ‘exteriority’ of tribal regions, and issues of ‘lawlessness’ – it makes the case for a holistic understanding of law as the necessary prerequisite to understanding the difficulties that that the country’s law, state and the wider society are faced with. The second significant argument of the study emerges from this expansion of the subject matter of (socio)legal analysis. It is argued that a shift in the understanding of what constitutes law in the context of Pakistan logically leads towards a (re)consideration of the lenses and narratives generally employed to examine it. The identification, examination and problematisation of these narratives – which include the dominant state-oriented legal narrative and the legal positivistic approach, the Islamic law narrative, legal pluralistic approach and the ascendant discourse on human rights – formulate the second substantive part of the study. It is argued that these Narratives of law differ in terms of how they perceive the context, identify their priorities, frame the problems and then propose solutions for their rectification. However, caught in a struggle to maintain their definitional consistencies, these narratives are only able to adopt a partial view of the picture and, owing to that, they generate contradictions that ultimately weaken their approach and proposed solutions. The purpose behind these two arguments is both to make a case for new avenues of context-specific legal analysis, as well as to create possibilities for it in the case of Pakistan. The problems that the country faces and the suffering that its people experience create an urgent need to recognise the deficiencies, both in our conceptualisation of law in this particular context, as well as the narratives, perspectives, theories and ideologies that we employ to approach it. This necessitates the search for alternative narratives for comprehending Pakistan’s socio-legal situation, to offer more nuanced approaches that might enable us to frame issues differently. This, I argue, is the most pressing task for those engaged in the analyses of legal, social and political spheres of Pakistan, and the necessary first step if our goal is the (re)formation of the legal and normative orders to make them more accountable to the people. By adopting the framework of colonialism and Coloniality to offer a different lens to understand Pakistan’s socio-legal peculiarities, the study presents one such attempt in this vein, with the purpose of initiating discussion and inviting critique.